Philippine education quality or quantity. - Velez, Jose Mari (Velez this week)
A look into the educational system in the country, where it succeeds and where it fails. Factors such as cost of education, the types of schools and the teachers' incompetence play a significant role in the success and failure of the country's educational system. Features the Education Subsidy Bill and the STFAP (Socialized Tuition and Financial Assistance Program) of the University of the Philippines.